NGS-Based Metagenomic Approaches for Bacterial Community Analysis: A Review - Hayati, Rifda; Marlina, Marlina; Agustien, Anthoni (Jurnal Biologi Tropis, 2026)
Microorganisms play a crucial role in biological, ecological, and biogeochemical processes; however, most environmental microorganisms cannot be readily grown under standard laboratory conditions, driving the development of Next-Generation Sequencing (NGS)-based metagenomic approaches that enable culture-independent characterization of microbial communities directly from environmental DNA. This review synthesizes the principles of NGS-based metagenomics, contrasts amplicon and shotgun approaches, compares major sequencing platforms and platform-selection criteria, and evaluates the applications and limitations of bacterial community analysis across the health, agricultural, and food sectors—an integration not commonly addressed together in previous reviews. Based on literature from 2018–2026 in PubMed/MEDLINE, Scopus, Web of Science, and Google Scholar, amplicon and shotgun metagenomics were found to offer complementary taxonomic and functional resolution, while platform choice depends on accuracy, read length, and budget. Across sectors, metagenomics supports pathogen surveillance and gut microbiome profiling in health, soil microbiome-based sustainability indicators in agriculture, and fermentation microorganism and antimicrobial resistance gene detection in food safety. Nevertheless, challenges remain regarding the accuracy of function prediction from amplicon-based data, bioinformatics pipeline standardization, and the validation of predicted microbial functions through complementary multi-omics approaches.